Children's mental health policies in the United States: perspectives from advocates and state leaders. (3rd April 2014) - Cooper, Janice L.; Aratani, Yumiko
Abstract: Background: Previous research suggests a disconnect on both policy and practice between advocates and state leaders in child mental health. Aim: To compare advocates' and state leader's perspectives and understanding on the three main themes in children's mental health policies: (i) state's initiatives to empower and engage families and youth in policy and practice; (ii) state's fiscal support for family and youth driven services; and (iii) policy challenges to improving children's mental health services and outcomes. Study design: This study draws on data from national surveys of State Children's Mental Health Directors (2006) and of state affiliates of Mental Health America (2007). Results: The findings from 38 responses representing 19 states suggest differences between state leaders and advocates on their understanding of family and youth engagement, service access, quality and fiscal supports. While state directors and advocates seem to have similar understanding on the existence of states' efforts related to evidence‐based practices, many advocates are unaware of the specifics of the strategies that states undertook or funded. Advocates also did not know which types of settings were eligible for reimbursement for children's services. Conclusions: Advocates lack some information that is vital to fulfilling their role. Policymakers seem unaware of key challenges that families face and therefore appear to be without critical information that fuels the agenda for advocates. The challenge for both set of actors is how to get beyond this information asymmetry to advance efforts to improve mental health.